Adoption of New Technology Vaccines - Zimmermann, Laura; Somasundaram, Jeeva; Saha, Barsha (Journal of Marketing, 2024)
Extensive research has examined the diffusion of innovations for products that can be trialed, and where the most adverse outcome, if a product fails, is a financial loss. However, less research has explored consumer responses to innovations in highly uncertain contexts characterized by health losses, lack of trialability, and the opportunity to free ride on other's adoption. This research focuses on vaccine decision making as a unique case within such contexts and extends the findings to other domains. Four studies (N total = 1,796; five supplementary studies, N total = 643) test the propositions of a formal model that incorporates uncertainty and others' choices into the adoption decision. The results show that consumers are surprisingly averse to products that are described as employing a new technology (e.g., mRNA technology) and require an “efficacy premium” to compensate for higher perceived uncertainty. However, considerable heterogeneity exists due to individual differences in technology readiness, trust in government, and risk attitudes. Notably, despite the prominent threat of free riding, a social proof nudge (communicating increasing population adoption) effectively reduces aversion to new technology. In this context, social proof information does not merely drive conformity or social learning, but instead increases adoption of new technology by alleviating perceived uncertainty.